Nonlinear Analysis Of Failure Mechanism Of Roller Compacted Concrete Dam - Abdul Malik Thanoon, Huda (2008)

(untitled)
Seismic effects have frequently caused damage to concrete dams. The consequences of a large dam failing can be disastrous, due to large amounts of damage of properties and human lives. Thus, there has been growing work on the safety evaluation of dams. In this study, seismic hazard assessment of roller compacted concrete (RCC) gravity dam is investigated by considering the effects of dam-reservoir-foundation-sediment-interface interaction. Using finite and infinite element coupled method; two-dimensional seismic analysis is performed to investigate the seismic response of RCC gravity dam. An existing finite element code was modified to include mathematical models to simulate the behavior of discontinuities on the response of the structural system subjected to static and seismic loadings. The discontinuity was modeled by thin layer interface element and formulated to model the contact area along RCC dam-flexible bedding foundation. The discontinuous deformation elasto-plastic computational mechanics was evolved based on the modified Mohr-coulomb criteria to simulate the behavior of thin layer interface. Safety evaluation is carried out based on the seismic performance and damage criteria, with special emphasis on the deformation behavior at dam–foundation thin layer interface. The results of nonlinear elasto-plastic analysis demonstrate that the maximum tensile stress occurs at the base of the dam on the upstream heel. Moreover, there is a redistribution of the stresses at thin layer interface with significant stresses reduction; this is due to the release of energy through different mode of deformation in this region. The results demonstrate that the plastic deformation in thin layer interface is allowed to occur whenever seismic stresses exceed the envelope presented by modified Mohr-Coulomb failure criteria and it is mainly in the slipping mode at thin layer interface elements. It is shown from the numerical results, that the computational mechanics was feasible to predict the nonlinear behavior of discontinuities. The results indicate that the modified finite element formulation can provide satisfactory and consistent analysis of thin layer interface behavior under static and seismic excitation. The major advantage of such a formulation is that it permits the computer programming and allows representation of the deformation modes for thin layer, such as debonding, slipping and crushing. Furthermore, this study examines the earthquake response of RCC gravity dam including comprehensive failure criteria of materials with modeling of cracking and crushing of concrete. Considerable effort has been devoted to include the failure criteria for thin layer interface element in terms of opening and slipping. The finite element code was developed to include a numerical procedure for computing the nonlinear dynamic response of RCC dam and the failure mechanism for thin layer interface element. The numerical results demonstrate that cracking develops near the base at dam heel and at upstream dam face especially around the opening of the galleries. Then the crack at the neck near the discontinuities is appeared and extended at the slope of the downstream face. Furthermore, the results demonstrate that the mode of failure in thin layer interface elements were opening and slipping. The implemented procedure into finite element code shows that the seismic cracking can be traced and mode of failure of RCC concrete gravity dam and at thin layer interface can be ascertained.